2017
DOI: 10.1093/gji/ggx073
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Gradiometry using Ambient Seismic Noise in an Anisotropic Earth

Abstract: We introduce a wavefield gradiometry technique to estimate both isotropic and anisotropic local medium characteristics from short recordings of seismic signals by inverting a wave equation. The method exploits the information in the spatial gradients of a seismic wavefield that are calculated using dense deployments of seismic arrays. The application of the method uses the surface wave energy in the ambient seismic field. To estimate isotropic and anisotropic medium properties we invert an elliptically anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Their results fitted well with their seismically derived compaction map (which does not show the center of the array due to there being a seismically obscured area in the center of the array). The ringed structure of the velocity and Q at the Ekofisk array can also be observed in surface wave group velocity tomography (de Ridder et al, ; de Ridder & Biondi, ), surface wave phase velocity tomography (de Ridder & Biondi, ; de Ridder & Curtis, ), and compressional and shear wave velocity (Kazinnik et al, ) estimates at the site.…”
Section: Geological Interpretationmentioning
confidence: 86%
See 1 more Smart Citation
“…Their results fitted well with their seismically derived compaction map (which does not show the center of the array due to there being a seismically obscured area in the center of the array). The ringed structure of the velocity and Q at the Ekofisk array can also be observed in surface wave group velocity tomography (de Ridder et al, ; de Ridder & Biondi, ), surface wave phase velocity tomography (de Ridder & Biondi, ; de Ridder & Curtis, ), and compressional and shear wave velocity (Kazinnik et al, ) estimates at the site.…”
Section: Geological Interpretationmentioning
confidence: 86%
“…Subsidence will likely cause fracturing of the rock, which may cause a reduction in Q. Surprisingly, the Q values seem to show little relation to the large-scale subsidence (even though the group and phase velocities and also their anisotropy are clearly related to subsidence (see Figure 7 and also Barkved et al, 2005;de Ridder et al, 2015;de Ridder & Curtis, 2017). There is a suggestion of a relation in the north of the 1 Hz plot, but nowhere else.…”
Section: Geological Interpretationmentioning
confidence: 96%
“…De Ridder and Biondi [48] demonstrated that such methods, which are closely related to the wave gradiometry technique, can be successfully applied to short recordings of ambient seismic noise to image the local velocity structure without the need to compute cross-correlations of long noise records. De Ridder and Curtis [49] extended the method to also yield anisotropic wavefield parameters.…”
Section: Single-station 6dof Wave Parameter Estimationmentioning
confidence: 99%
“…De Ridder and Curtis (2017) deduced a second‐order anisotropic elliptic equation of high‐frequency noise surface wave energy based on information on wave gradients and then estimated the azimuthal anisotropy of the shallow surface of the Ekofisk. The second‐order spatial gradient can generally reduce truncation errors, but it works best for a rectangular array.…”
Section: Introductionmentioning
confidence: 99%